Recent progress in transition-metal-catalyzed enantioselective indole functionalizations - Chen, Jing-Biao; Jia, Yi-Xia (Organic & biomolecular chemistry, 2017)
Numerous efficient synthetic methods for enantioselective indole functionalizations have emerged in recent years. This review summarizes the major achievements in the transition-metal-catalyzed enantioselective indole functionalization reactions since 2010 and focuses on C-C bond formation processes, including alkylations, arylations, cycloaddition reactions, and other reactions. It intends to give a compendious overview of the significant progress achieved in this area. Recent progress on the transition-metal-catalyzed enantioselective functionalization reaction of indoles is reviewed, which is mainly focused on asymmetric indole alkylations, arylations, cycloaddition reactions, and other reactions.